Study of antioxidant properties of food additives obtained from secondary vegetable resources in testing laboratory animals - N. N. Kornen (Новые технологии, 2017)
The data describing the composition of antioxidants contained in food additives obtained using innovative technologies from secondary plant resources formed at fruits and vegetables processing are given. It has been established that the researched food additives provide a reliable decrease in the mass fraction of malonic dialdehyde and diene conjugates in the blood serum of animals of the experimental groups as compared to the control group of animals. The obtained data allow drawing a conclusion that the researched food additives exhibit antioxidant properties. It’s been revealed that food additives exhibit hepatoprotective properties, along with antioxidant properties, characterized by a significant decrease in the level of activity of liver enzymes. By the degree of manifestation of these properties, the researched food additives can be arranged in a row (in descending order): “Grape seeds powder” ® “Apple powder”® “Pumpkin powder”.